Phase 2 prospective open label study of neoadjuvant nab‐paclitaxel, trastuzumab, and pertuzumab in patients with HER2‐positive primary breast cancer. Issue 5 (14th December 2022) - Lavasani, Sayeh M.; Somlo, George; Yost, Susan E.; Frankel, Paul H.; Ruel, Christopher; Cui, Yujie; Murga, Mireya; Tang, Aileen; Martinez, Norma; Kruper, Laura; Tumyan, Lusine; Schmolze, Daniel; et al.
Abstract: Background: The objective of this study was to evaluate the safety and efficacy of nab‐paclitaxel, trastuzumab, and pertuzumab as neoadjuvant therapy (NAT) in patients with human epidermal growth factor receptor 2 HER2+ breast cancer (HER2+ BC) to determine pathologic complete response (pCR), invasive disease‐free survival (iDFS), and overall survival. Methods: Forty‐five patients with HER2+ BC Stages II–III were to be enrolled from 2013 to 2017. Patients were treated with weekly nab‐paclitaxel (100 mg/m 2 intravenously), weekly trastuzumab (4 mg/kg loading dose, then 2 mg/kg), and six cycles of pertuzumab (840 mg loading dose, then 420 mg intravenously day 1 every 21 days). Results: Median follow‐up was 60 months (95% CI, 32.3–55.6) and pCR was 29/45 (64%). The 5‐year iDFS for patients who achieved pCR ( N = 29) was 96.3% (95% CI, 76.5–99.5) and non‐pCR patients ( N = 16) was 74.3% (95% CI, 39.1–91.0). The 5‐year overall survival ( N = 45) was 94.1% (95% CI, 77.6–98.5). Based on hormonal status, the 5‐year iDFS for HR+ pCR patients ( N = 14) was 92.3% (95% CI, 56.6–98.9) and for HR− ( N = 15) was 100% ( p = .3). Conclusions: This anthracycline/carboplatin‐free regimen with nab‐paclitaxel achieved a pCR rate of 64% in patients with HER2+ BC. The 5‐year iDFS in patients with and without pCR was 96.3% and 74.3%, respectively. The pCR rate is comparable with docetaxel, carboplatin, trastuzumab, and pertuzumab therapy in the NAT setting, but with fewer treatment‐associated toxicities. This finding suggests the possibility of safe avoidance of anthracyclines and carboplatin as components of NAT in patients with HER2+ BC. Abstract : This anthracycline/carboplatin‐free regimen with nab‐paclitaxel achieved a pathologic complete response rate of 64% in patients with human epidermal growth factor receptor 2 breast cancer (HER2+ BC). This finding suggests the possibility of safe avoidance of anthracyclines and carboplatin as components of neoadjuvant therapy in HER2+ BC patients.